1998
DOI: 10.1177/107110079801900903
|View full text |Cite
|
Sign up to set email alerts
|

Modified Mitchell Osteotomy for Hallux Valgus

Abstract: From 1988 to 1995, 96 patients (161 feet) underwent a modified Mitchell distal metatarsal osteotomy performed for mild-to-moderate hallux valgus. On AP x-rays of the standing foot, the average intermetatarsal angle was corrected from 15 degrees to 9 degrees, and the first metatarsophalangeal angles were corrected from an average of 41 degrees to 15 degrees. Criteria for evaluation of clinical results included relief of pain, appearance of foot, and shoe wear. After an average follow-up of 38 months, the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 19 publications
1
24
1
Order By: Relevance
“…Good correction of the deformity has been reported. 33,34 Nevertheless, shortening of the first metatarsal occurs due to removal of bone to create the stepcut. This, combined with a lack of inherent stability resulting in dorsal malunion, has led to reports of transfer metatarsalgia in between 10% and 30% of patients.…”
Section: Distal Metatarsal Osteotomiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Good correction of the deformity has been reported. 33,34 Nevertheless, shortening of the first metatarsal occurs due to removal of bone to create the stepcut. This, combined with a lack of inherent stability resulting in dorsal malunion, has led to reports of transfer metatarsalgia in between 10% and 30% of patients.…”
Section: Distal Metatarsal Osteotomiesmentioning
confidence: 99%
“…This, combined with a lack of inherent stability resulting in dorsal malunion, has led to reports of transfer metatarsalgia in between 10% and 30% of patients. 33,35 Loss of correction can also occur. Some authors have reported a decrease in these complications by the use of internal fixation in order to increase stability.…”
Section: Distal Metatarsal Osteotomiesmentioning
confidence: 99%
“…2 Mild deformities are usually corrected with a distal osteotomy, while moderate and severe deformities are corrected with diaphyseal or proximal osteotomies. 3,4 Despite several techniques for hallux valgus correction, there is much controversy regarding the best procedure to use in a severe deformity, 5 Mitchell and Scarf osteotomies do not restore the load bearing function of the foot to normal, 6 Mitchell's osteotomy appears to be performed in a variety of different ways 7 , some modifications, such as the planter displacement of the metatarsal head has been shown to be important. 8…”
mentioning
confidence: 99%
“…In other studies that used open techniques in association with soft tissue procedures, the recurrence rate ranged from 0% to 10%. (17,51,52,53) Although some of our cases had an increase in HVA after K -wire removal, the HVA and first IMA were significantly decreased at final follow -up. The Kirschner wire insertion level in the study of Yu-Chuan Lin et al was at the middle of the proximal phalanx.…”
Section: Discussionmentioning
confidence: 93%
“…(52,54) This may be explained by lengthening of the first metatarsal through an oblique distally oriented osteotomy (dorsal arm) and excessive medial capsular tightening may lead to impaired range of motion of the MPI joint. However, this problem can be treated by early passive mobilization of the MPI joint.…”
Section: Discussionmentioning
confidence: 99%